New records of helminths parasitic on Peruvian Amazonian. fishes (Osteichthyes) - Iannacone, José A.; Luque, José L. (Revista de Biología Tropical, 1993)
The document shows new records of parasitic helminths in fish of the Peruvian Amazon.